Manifestation of Identity among Diaspora Groups in Russian Multiethnic Region (on Example of Bashkortostan Jews) - F. G. Safin; E. N. Sabirova; K. O. Sirazetdinov (Научный диалог)
The problems of identity manifestation in ethno-disperse groups, in particular Jews, in the Republic of Bashkortostan as one of the polyethnic Russian regions are considered. The study is based on the analysis of ethnolinguistic identity of Jews in the region in the late 19th, during 20th and early 21st centuries. It is noted that in the late 19th - early 20th centuries the ethnolinguistic identity of the Jewish population remained very high, but during the Soviet period, living in a multi-ethnic Republic, highly urbanized Jewish ethnic group, adapting to the local Russian-speaking environment, largely lost the native language of their nationality. Based on the results of a comparative analysis of the all-Union and all-Russian population censuses, it is proved that, despite the measures taken to revive the native languages, in the post-Soviet period, compared with the Soviet one, Jewish ethno-disperse group had no special changes in the ethnolinguistic identity - the recognition of the Jewish language as a native language remained very low. It is emphasized that the Jewish population living in Bashkortostan unlike representatives of other ethnic groups in the region (Bashkirs, Tatars, Russians, etc.), is mostly aware of the all-Russian identity more than regional.